Design and Prototype of Mobile Robots for Rescue Operations - Keçeci, Emin Faruk; Keçeci, Emin Faruk (Cambridge University Press, 2009)
This study concerns the design and prototype of four different mobile robot platforms for rescue robot operations after an earthquake. At first, a test field is constructed to represent a mildly damaged earthquake zone. The test field consists of eight different sections: sand, gravel, ditch, water, bridge, incline, decline, and turn. The mechanical structure, electronics, software, communication, and possible sensory systems are explained. After the robots are manufactured, they are physically tested for their performance in the test field for 18 different parameters. The test results show the effective body structure. Challenges of the rescue robot design are explained and future expectations are given.
Keywords: Machine design; Rescue robotics; All terrain; Prototype robot design